2017
DOI: 10.1142/s0192415x1750077x
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol Reduces Renal Ischemia and Reperfusion Injury via Inhibition of Apoptosis

Abstract: Magnolol, a constituent of the bark of Magnolia officinalis, has been reported to decrease myocardial stunning and infarct size. In this study, we investigated whether magnolol can reduce renal ischemia and reperfusion (I/R) injury. Renal I/R, induced by a 60-min occlusion of bilateral renal arteries and a 24-h reperfusion, significantly increased blood urea nitrogen (BUN) and creatinine levels, and caused histological damage to the kidneys of rats. Apoptosis, as evaluated by terminal deoxynucleotidyl transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…However, reports are inconsistent. One study noted that IR does not increase the concentrations of these cytokines ( Zhu et al, 2014 ), whereas other studies have reported increases in cytokine concentrations in proportion to the severity of injury ( Shen et al, 2018 ; Tang et al, 2017 ; Zhang et al, 2018 ; Zhang et al, 2015 ). In this work, we did not observe significant increases in the concentrations of IL-1β, IL-6, or TNF-α.…”
Section: Methodsmentioning
confidence: 99%
“…However, reports are inconsistent. One study noted that IR does not increase the concentrations of these cytokines ( Zhu et al, 2014 ), whereas other studies have reported increases in cytokine concentrations in proportion to the severity of injury ( Shen et al, 2018 ; Tang et al, 2017 ; Zhang et al, 2018 ; Zhang et al, 2015 ). In this work, we did not observe significant increases in the concentrations of IL-1β, IL-6, or TNF-α.…”
Section: Methodsmentioning
confidence: 99%
“…Five random fields per slide (five slides per animal, seven animals per group) were examined. The number of TUNEL-positive cell nuclei (numerator) and the total number of cell nuclei (denominator) were counted as previously described [46]. The percentage of TUNEL-positive cells in each field was analyzed using Image-Pro Plus 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…MAG is reported to possess an array of pharmacological effects including anti-oxidant [70], anti-inflammatory [71], anti-bacterial [10], anti-thrombotic or anti-platelet [72], anti-stress [73], anti-anxiety, anti-Alzheimer [74], anti-stroke [75], hypoglycemic [76], smooth muscle relaxant [77,78], weight control [79], anti-dyspeptic/prokinetic [80], anti-epileptic [81], and hepatoprotective effects [82]. Small-scale clinical studies on MAG and its interaction with gamma-aminobutyric acid-A (GABA-A) and muscarinic receptors show that it helps in decreasing the anxiety levels in patients [78,83,84,85].…”
Section: Biological Activities Of Magnololmentioning
confidence: 99%